2018
DOI: 10.3390/ijerph15030418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sexual Dimorphism on Trauma Patterns and Clinical Outcomes of Patients with a High-Risk Score of the Osteoporosis Self-Assessment Tool for Asians: A Propensity Score-Matched Analysis

Abstract: The Osteoporosis Self-assessment Tool for Asians (OSTA) is a validated index based on age and weight to predict the risk of osteoporosis in women. This cross-sectional study was designed to evaluate the impact of sexual dimorphism on the trauma patterns and the clinical outcomes of patients with high-risk OSTA scores. Trauma data of patients with high-risk OSTA scores between 1 January 2009 and 31 December 2015 were retrieved from the trauma registry system of a level I trauma center. A total of 2248 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Elderly individuals are at the greatest risk of a fall accidents [1,2] and their consequences, such as fractures, immobility, and sometimes even death [3][4][5][6][7]. In addition to pain, a femoral fracture results in a curtailment of physical activity, increased dependence, and rapid worsening of the health status.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly individuals are at the greatest risk of a fall accidents [1,2] and their consequences, such as fractures, immobility, and sometimes even death [3][4][5][6][7]. In addition to pain, a femoral fracture results in a curtailment of physical activity, increased dependence, and rapid worsening of the health status.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, females accounted for a small proportion (25.9%) of skull fracture patients, which is consistent with the results of a previous study that revealed gender differences in head trauma [ 5 , 28 ]. Our previous studies also reported that more males than females sustained TBI in road accidents [ 18 , 29 ]. The study results did not identify gender as a significant risk factor for mortality, which is in accordance with reports from other studies [ 10 14 ].…”
Section: Discussionmentioning
confidence: 82%
“…The study double-coded the injuries for all 7520 consecutively admitted trauma patients during a three-year period between 1 January, 2016, and 31 December, 2018, by two certified specialists who had been trained for coding and experienced for three and ten years, respectively, in trauma registry at Taiwan. The study hospital is a level I trauma center in the Kaohsiung city, Taiwan [18][19][20] and serves around three millions patients in southern Taiwan with another two level I trauma centers [21][22][23][24]. About thirty thousand trauma patients had visited the emergency department of this hospital and, among them, there were around 3600 hospitalizations per year.…”
Section: Study Populationmentioning
confidence: 99%